Experimental models of cortical multiple sclerosis pathology. (2017) - Witte, Maarten E.; van Horssen, Jack
Abstract : Grey matter tissue damage is a characteristic pathological hallmark of multiple sclerosis. Although evidence is emerging that cortical atrophy is strongly associated with sustained disease progression, the underlying pathological processes that contribute to neurodegeneration remain poorly understood. One reason for this is that key features of progressive MS, such as cortical demyelination, microglial cell activation and neurodegeneration are absent in most of the commonly used rodent MS models. In this short review we will provide an overview of experimental MS animal models that exhibit MS-like cortical pathology. These models will be instrumental in unravelling the pathogenic mechanisms that contribute to cortical pathology and testing the efficacy of neuroprotective therapies for progressive MS patients.